Between innovative and habitual behavior. Evidence from a study on sustainability in Greece, Poland, Portugal, Sweden, and the United Kingdom - Baran, Małgorzata; Hazenberg, Richard; Iwińska, Katarzyna; Kasianiuk, Krzysztof; Perifanos, Ioannis; Ferreira Da Silva, Joana Maria; Vasconcelos, Clara (Frontiers in Energy Research, 2023)
In this article, we explore individuals’ pro-environmental innovative behavior (PEIB) as one of the conditions for developing more sustainable cities. We assume that energy-efficient sustainable cities are those where people behave sustainably. Hence, studying the conditions of human behavior is essential for understanding the transformation of cities. We focused on individual antecedents of pro-environmental innovative behavior with a survey conducted in five European countries and a sample of 2502 participants. Descriptive and correlation statistical analyses confirm a moderate relationship between environmental awareness and environmental action. Based on this rudimentary analysis, we suggest further research on city energy transformation, including multiple aspects of individual behavior.